THE EFFECTIVENESS OF COGNITIVE-BEHAVIORAL THERAPY IN ADOLESCENTS WITH SOCIAL ANXIETY DISORDER - Pedro do Valle Varela, João; Filipe Silva Oliveira, Luís; Edas Corteletti Pereira Lopes, Victor; Gaspar Calzolari, Júlia; Maria Eccard André, Andresa; Teófilo da Silva, Kaicki; Djosci Coêlho de Sá, Henrique; Carlos Mendes Campos, Walter; Marcelo Pacheco Kokis, João; Peçanha Souza, Igor (Health and Society, 2024)
Social anxiety disorder (SAD) is a prevalent condition among adolescents, characterized by an intense and persistent fear of social situations or performance, which results in significant distress and impairment in daily activities. Adolescents with SAD often avoid social interactions, which can negatively affect their academic, social and emotional development. Cognitive-behavioral therapy (CBT) has been widely recognized as an effective approach to treating SAD, offering practical strategies to reduce anxiety symptoms and improve social functioning. This abstract will explore the effectiveness of CBT in adolescents with social anxiety disorder, highlighting the main techniques used and the clinical outcomes observed. The aim of this paper is to review and evaluate the effectiveness of cognitive-behavioral therapy in the treatment of adolescents with social anxiety disorder. The aim is to analyze the main techniques of CBT, the mechanisms by which it promotes anxiety reduction and the results of clinical studies that show its effectiveness. In addition, the challenges and specific considerations in applying CBT to this age group will be discussed. This literature review aims to analyze the effectiveness of Cognitive-Behavioral Therapy (CBT) in the treatment of social anxiety in adolescents. To this end, references from relevant studies and meta-analyses were selected and reviewed, covering various approaches and results related to the topic. The selection of references was based on the relevance and impact of the publications in the field of psychotherapy and social anxiety. CBT is a form of psychotherapy based on identifying and modifying dysfunctional patterns of thought and behavior. In the context of SAD in adolescents, CBT aims to help patients recognize and restructure irrational beliefs about themselves and social situations, develop appropriate social skills and reduce avoidance of social interactions. With this in mind, the main CBT techniques include cognitive restructuring, gradual exposure and social skills training. Cognitive restructuring involves helping adolescents to identify negative automatic thoughts and replace them with more realistic and balanced interpretations. Gradual exposure consists of exposing adolescents, in a controlled and progressive way, to feared social situations, allowing them to face their fears and reduce the associated anxiety response. Social skills training focuses on developing social competencies, such as initiating and maintaining conversations, asking and answering questions, and dealing with criticism and rejection in an assertive manner. Clinical studies have demonstrated the effectiveness of CBT in reducing SAD symptoms in adolescents. Research indicates that adolescents who receive CBT show a significant decrease in levels of social anxiety, improved quality of life and greater participation in social and school activities. For example, a study conducted by Masia Warner et al. (2005) showed that adolescents who participated in a group CBT program had a notable reduction in social anxiety symptoms compared to a control group. Another study by Beidel, Turner and Morris (2000) showed that individual CBT resulted in substantial improvements in adolescents’ social anxiety and social functioning. Despite the promising results, the application of CBT to adolescents with SAD presents specific challenges. Adherence to treatment can be hampered by adolescents’ resistance to engaging in therapy sessions and facing feared social situations. In addition, parental involvement and coordination with schools are important components for successful treatment, as social and environmental support is crucial for the generalization of therapeutic gains. Therefore, cognitive-behavioral therapy has proven to be an effective approach for treating adolescents with social anxiety disorder. Cognitive restructuring techniques, gradual exposure and social skills training are key to helping adolescents overcome their fears and improve their social functioning. Clinical studies provide robust evidence that CBT can significantly reduce SAD symptoms and improve quality of life for adolescents. However, it is essential to consider the challenges specific to this age group, including resistance to treatment and the need for support from parents and schools. With a careful and collaborative approach, CBT can provide lasting benefits for adolescents with social anxiety disorder, promoting their emotional and social well-being.